Physical Metallurgy Inspired Nano‐Features for Enhancement of Thermoelectric Conversion Efficiency. Issue 9 (19th July 2018) - Amouyal, Yaron; Gelbstein, Yaniv; Fuks, David
Abstract: Thermoelectric (TE) materials are useful for the conversion of heat flux into electrical power and for heat removal and are, therefore, technologically important. Development of TE materials involves controlling their thermal and electrical transport, and both are sensitive to the finest features of the material microstructure. Major turning points recorded in TE material research are enabled due to adopting concepts from physical metallurgy. These classical approaches, originally developed to explain plastic deformation mechanisms in metallic systems, are now being employed to elucidate thermal and electrical transport in highly efficient TE materials, and serve as tools to manipulate their transport properties. The present Progress Report reviews recent studies combining experimental and computational approaches aiming to elucidate the role of 0D, 1D, 2D, and 3D lattice defects, and to harness them to enhance TE performance. Abstract : A commonly used approach to enhance thermoelectric efficiency adapted from physical metallurgy is the formation of highly dispersed precipitates in the matrix for phonon scattering. Selection of the appropriate alloy composition, and heat treatment temperature and duration, enables delicate control of the microstructure evolution kinetics, thereby achieving minimum lattice thermal conductivity.